Species turnover in the Swedish bird fauna 1850–2009 and a forecast for 2050 - Haas, Fredrik; Barbet-Massin, Morgane; Green, Martin; Jiguet, Frédéric; Lindström, Åke (Ornis Svecica, 2014)
There is presently great concern about local, regional and global loss of species. We examined those breeding species and subspecies (“species”) of birds that either established themselves or went extinct in Sweden in 1850–2009. In this period Sweden got 38 new and lost twelve breeding bird species. The average (and surprisingly steady) rate of colonization was 2.4 species per decade, which was three times higher than the rate of extinction of 0.75 species per decade. We also predict future establishments and extinctions until year 2050, based on Species Distribution Modelling and recent information from neighbouring countries. We find it probable that eleven new species will join the Swedish avifauna until 2050 and possible that another nine species will do so. The predicted rate of probable establishment is 2.9 species per decade. We identified seven species/subspecies to be at risk of extinction by 2050. The future in Sweden for several of these species is probably dependent on the success or failure of ongoing conservation programs. There seems to be no immediate threat of establishment of alien species.